Organizational Social Capital in InterOrganizational Project: A study developed in the Third Sector - Tondolo, Rosana da Rosa Portella; Bitencourt, Claudia Cristina; Vaccaro, Guilherme Luís Roehe (Revista de Administração da UFSM, 2017)
Third Sector Organizations have emerged with the purpose of finding solution to different kinds of social problems. These organizations are challenged to keep their activities and achieve organizational sustainability basically gathering founds from third parties, which are derived from donations, partnerships, agreements, among others. In this sense, this study aimed to identify the level of Organizational Social Capital (OSC) of social organizations that participated of an interorganizational project developed in the Rio Grande do Sul State, Brazil. In this regard, it was conducted a quantitative survey using cluster analysis and non-parametric tests such as Kruskal-Wallis and Wilcoxon-Mann-Whitney. The main contributions of this study are the classification of 3 groups with different levels of CSO, and the reflection on the motivations and reasons for the existence of these three different groups regarding level of CSO. This study showed the respondent bias as a limitation. Finally, it is suggested directions for future studies, which consider the examination of the variables shared vision 2 and trust 2, and the relationship between the levels of CSO and how the resources are mobilized by organizations.